Long-Term Exercise Alters the Profiles of Circulating Micro-RNAs in the Plasma of Young Women - Li, Fan; Bai, Muwei; Xu, Jianfang; Zhu, Ling; Liu, Chengyi; Duan, Rui (Frontiers in Physiology, 2020)
OBJECTIVES: To study the effects of long-term exercise on circulating microRNAs in human plasma. METHODS: Whole blood was collected from 10 female elite athletes with at least 5 years of training experience in the Chinese National Synchronized Swimming Team (S group) and 15 female college students without regular exercise training (C group). Plasma miRNAs were then isolated, sequenced and semi-quantified by the second-generation sequencing technology, and the results were analyzed by bioinformatics methods. RESULTS: We found 322 differentially expressed miRNAs in S group compared with C group, among which 216 miRNAs were up-regulated and 106 were down-regulated. The top five abundant miRNAs in the 322 miRNAs of the S group are hsa-miR-451a, hsa-miR-486, hsa-miR-21-5p, hsa-miR-423-5p and hsa-let-7b-5p. Muscle-specific/enriched miRNAs were not significantly different except miR-206 and miR-486. According to the Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis, a large proportion of the differentially expressed miRNAs targeted in cancer-related pathways, including proteoglycans in cancer, miRNAs in cancer and basal cell carcinoma. As levels of the ci-miRNAs are commonly known to be significantly deregulated in cancer patients, we further compared the levels of some well-studied miRNAs in different types of cancer patients with those in S group, and found that long-term exercise regulates the level of ci-miRNAs in an opposite direction to those in cancer patients. CONCLUSIONS: Long-term exercise significantly alters the profiles of plasma miRNAs in healthy young women. It may reduce the risk of certain types of cancers by regulating plasma miRNAs levels.